Q:

Given: 3x = 5 (x − 4) Prove: x = 10========================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10

Accepted Solution

A:
Answer:see the procedureStep-by-step explanation:we have[tex]3x=5(x-4)[/tex]step 1[tex]3x=5(x-4)[/tex] ------> given problemstep 2Applying the Distributive Property right side[tex]3x=5(x)-5(4)[/tex][tex]3x=5x-20[/tex]step 3Applying the Subtraction Property of EqualitySubtract (3x-20) both sides[tex]3x-(3x-20)=5x-20-(3x-20)[/tex][tex]20=2x[/tex]step 4Applying Division Property of EqualityDivide by 2 both sides[tex]20\2=x[/tex]Rewrite[tex]x=10[/tex]